Analytical review on Effect of 3D printing parameters on Mechanical properties of ABS and nanofillers - Ashwini A Mate; Dr.D.N.Raut (Utilitas Mathematica, 2025)
The rapid advancement of 3D printing technology has enabled the production of complex and customized parts across various industries. Acrylonitrile materials utilized in 3D printing, Butadiene Styrene (ABS), graphene, and have garnered significant graphene oxide attention to their unique properties and potential applications. This review examines the influence of 3D printing and parameters on the mechanical properties of these materials. Key parameters such print speed, layer height, density, nozzle temperature, and bed temp explored to understand their impact on tensile strength, impact. Form ABS, optimized parameters enhance layer adhesion and reduce defects, resulting in improved mechanical properties. The incorporation of graphene and graphene oxide into 3D printing filaments demonstrates significant enhancements in tensile strength and stiffness, though optimization of dispersion and printing conditions is critical. A comparative analysis highlights the advantage and limitations of each material, emphasizing the need for tailored parameter settings to maximize performance. The review so discusses emerging trends and future research directions, the underscoring the potential of graphene based materials in advanced 3D the printing applications. The findings of this review provide valuable insights for researchers and practitioners aiming to optimize 3D printing processes and material performance.